KEMAMPUAN MENULIS SISWA KELAS XI SMA NEGERI 8 MAKASSAR - Said, Nurhayati (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2010)
This study aims to obtain data on essay writing skills in German of the students at SMA Negeri 8 Makassar. The population was the students at grade XI of SMA Negeri 8 Makassar. It used total sampling technique and data were collected by using tests and questionnaires. The tests were administered to measure the writing skills in German and the questionnaire was intended to obtain information about the factors that influence the writing skills in German. The data obtained were statistically analyzed by using percentage. The results showed that the average score obtained by the students in essay writing in German were 58.63%. There were 2 students (5.25%) failed, 21 students (55.26%) predicated poor, 11 students (28.94%) were categorized as adequate, and 4 students (10.52%) predicated as good. The factors that influence students’ writing were that writing is very difficult, the way of teacher present the lesson, students were lazy to write, lack of writing guidance given by the teacher.